Positive factors on survival of head and neck cancer of unknown primary: what the clinician can do - Khalil, Firas; Koch, Michael; Iro, Heinrich; Sievert, Matti; Haderlein, Marlen; Semrau, Sabine; Fietkau, Rainer; Agaimy, Abbas; Scherl, Claudia (Acta Oto-Laryngologica, 2023)
Background: Management of patients with head and neck cancer of unknown primary (HNCUP) is challenging. Aims/Objectives: To provide a long-term analysis focusing on protective survival factors for clinical decision-making. Furthermore, the prognostic value of the current N classification system was evaluated. Material and methods: We retrospectively analyzed patients with HNCUP between 2003 and 2016. Univariate and multivariate analyses were used to investigate predictors of overall survival (OS). Results: A primary tumor was found in 67 of 290 patients with suspected HNCUP, leaving after exclusion 141 HNCUP cases for analysis, who received multi-step therapy (MST) (n = 108) or single therapy (n = 28). Chemotherapy (CT) (n = 101), curative MST, ≤3 positive lymph nodes (LN) (n = 33), squamous cell carcinoma (SCC) (n = 123), HPV+ (n = 21), M0 (n = 70) increased OS by 21.8%, 24.4%, 12.7%, 6.8%, 18.7%, 29.6%, respectively. 5- and 10-year OS was 78.1%/66.6%. The number of metastatic LNs predicted OS is better than N classification. Conclusion and significance: Aspects for clinical decision-making: Curative MST and SCC histology were the most significant predictors for improved OS. Categorizing LN into 1, 2-3, and >3 LNs was more significant than the traditional N classification. The addition of CT to curative MST has a stronger impact on survival than HPV and N classifications.
CRIS-Team Scopus Importer:2023-10-27
Keywords: cancer; cancer of unknown primary; CUP; head and neck; hNCUP; hNSCC; squamous cell carcinoma; survival